Commissural alignment in transcatheter aortic valve replacement: A literature review - Khalid, Abdul Muiz; O'Sullivan, Crochan J. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Transcatheter aortic valve replacement (TAVR) is a minimally invasive procedure to replace a diseased and faulty aortic valve in patients with severe aortic stenosis. As TAVR gains popularity among lower-risk younger patients with a longer life expectancy; there is a need to investigate the long-term shortcomings and limitations of the procedure for this patient group. One such shortcoming is that commissural alignment of transcatheter heart valves (THV) appears to be random; meaning that the THV neo-commissures can misalign with the native commissures of the aortic valve during deployment or self-expansion. Objectives Identify techniques and procedures used to obtain commissural alignment in TAVR. Evaluate the effectiveness of these procedures in terms of the degree of commissural alignment. Analyse the impact of commissural alignment on coronary filling and re-access. Methods Two electronic online databases were searched to identify existing literature relevant to the aim and objectives of this review: EBSCOhost and PubMed. After search filters were applied and duplicates removed; a total of 64 articles from both databases were screened against the inclusion/exclusion criteria. This resulted in a total of thirteen articles which met the objectives of this review and thus; were included. Results All studies focused on a patient centered approach involving pre-TAVR computed tomography to obtain commissural alignment. Other studies modified this approach and combined techniques. All studies that implemented a technique to reduce commissural misalignment were significantly successful in obtaining commissural alignment when compared to a study in which alignment was random when no technique was implemented. Severe coronary overlapping in commissural aligned heart valves was relatively low compared to severe coronary overlapping when no technique was implemented. Conclusions An increase in optimal commissural alignment via introduction of an alignment technique may seem attractive; however; the categorization of commissural alignment is arbitrary and does not accurately reflect real life clinical implications. Further research is needed to determine whether a routine procedure to achieve commissural alignment is necessary in low-risk younger patients undergoing TAVR.